Cybernetics of the Poor, Diedrich Diederichsen and Oier Etxeberria (eds) (2021). Issue 2 (1st October 2021) - Arar, Raphael
Review of: Cybernetics of the Poor, Diedrich Diederichsen and Oier Etxeberria (eds) (2021)Dijon: Les Presses du réel, 264 pp., ISBN 978-3-95679-593-0, p/bk, $24.95